Answer:
<u>x = 36</u>
Step-by-step explanation:
180 - 126 = 54
90 + 54 + x = 180
144 + x = 180
180 - 144 = x
x = 36
Have a nice day!
Answer:
60
Step-by-step explanation:
It is just 60 I did my work lol
First, rearrange the equation so that it is solving for y:
3x - y = 1
+y +y
3x = y + 1
-1 -1
3x - 1 = y
Now substitute the domain values you have listed into the 'x' of the equation to get the values for y.
For example:
3(-3) - 1 = y
-9 - 1 = y
y = -10
Answer:
Step-by-step explanation:
-5.25+2.25 - 3
1-0.5 = 0.5
=-6 =m
y=-6x